L’impero (americano) colpisce ancora. La conversione forzosa dell’esercizio italiano alla proiezione panoramica (Schermi. Storie e culture del cinema e dei media in Italia, 2024)
At the end of the Second World War, the American film industry was able to quickly regain the large European market shares it had held in the second half of the 1930s. In Italy, potentially the most lucrative country on the continent, the goal is achieved through the extensive occupation of the ex-hibition chain: first, between 1945 and 1953, by saturating the market with an abnormal number of films, and then, from 1954, by beating the competition with a brand new generation of widescreen products filmed in CinemaScope, VistaVision and the like. However, in order to properly project Holly- wood’s widescreen productions, every Italian cinema had to undergo major renovations, as was the case with the widespread transition to talkies. The purpose of this paper is to examine the successful conversion of the Italian exhibition chain to widescreen technology in the context of Hollywood’s aggressive commercial foreign policy in the 1950s, using a film industry studies approach within the wider field of media industry analysis.